2004
DOI: 10.1300/j029v13n03_03
|View full text |Cite
|
Sign up to set email alerts
|

Examining Gender Differences in Adolescent Substance Abuse Behavior: Comparisons and Implications for Treatment

Abstract: This study investigates gender differences in adolescent substance abuse behavior, treatment effectiveness, and the associated relationships with pre-, during-, and post-treatment groups of variables. Analyses were performed using 6-month post-treatment follow-up data from over two thousand subjects. T-test analysis showed that females exhibited more psychological difficulties, family-related problems, and sexual abuse experiences, whereas males exhibited worse school and legal problems before treatment. Femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 40 publications
0
27
1
Order By: Relevance
“…In addition, differences in MA abuse among teen females and males may present different challenges to their health and may require different treatment approaches. Hsieh and Hollister (2004) have suggested, for example that interventions should be specific to gender, such that treatments for adolescent girls should address the potential for drug use as a medication (or emotional relief) and should promote appropriate coping skills (14).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, differences in MA abuse among teen females and males may present different challenges to their health and may require different treatment approaches. Hsieh and Hollister (2004) have suggested, for example that interventions should be specific to gender, such that treatments for adolescent girls should address the potential for drug use as a medication (or emotional relief) and should promote appropriate coping skills (14).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to peer influence on substance use varying based on the gender of the adolescents, there is also evidence suggesting the gender composition of a network can alter the strength of a network’s influence on substance use (Hsieh & Hollister, 2004; Leaper, Tenenbaum, & Shaffer, 1999; Rose & Rudolph, 2006). For instance, adolescents within a same-sex friendship/network will experience a mutual influence pattern, whereas those in mixed-sex friendships/networks will experience a disproportionate amount of influence depending upon several factors, such as friendship context and the predominant gender in the friendship/network (Gaughan, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In one study, Harrison and Asche (2001) studied 387 adolescents in 37 programs and found that females were more likely than males to complete treatment and to be abstinent from drug use after treatment. In another study, Hsieh and Hollister (2004) studied more than 2,000 adolescents and found that females had more psychological difficulties than males but had better treatment attendance and better outcomes. Finally, several studies have documented an association between comorbid psychopathology and substance use severity both at baseline and posttreatment Tomlinson, Brown, & Abrantes, 2004;Winters, Stinchfield, Latimer, & Stone, 2008).…”
Section: Discussionmentioning
confidence: 99%